Educational Unity and Student Development in The Process of Physical Education - N.M.Gafurov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses the educational unit in the process of physical education and the impact of physical education on student development Action games that help students develop physical abilities, movement skills and abilities in the process of physical education